Meanings of near-synonyms and their translation issues in the Holy Qur'ān - Abdul-Qader Khaleel Mohammed Abdul-Ghafour,; Norsimah Mat Awal,; Intan Safinaz Zainudin,; Ashinida Aladdin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Holy Qur'ān includes near-synonyms which have seemingly similar meanings but convey different meanings upon deeper analysis of the semantic constituents of these words. Such near-synonyms usually pose a challenge that often presents itself to the translators of the Holy Qur'ān. This study investigates the meanings of near-synonyms and their translation issues in the Qur'ān. It aims to identify the contextual meanings of Qur'ānic near-synonyms based on different exegeses of the Qur'ān. Then, it explains the nuances that exist between the pairs of Qur'ānic near-synonyms and how such nuances are reflected in two English translations of the Qur'ān. The study adopts the Relation by Contrast Approach to Synonyms (RC-S) as a theoretical framework for data analysis. It also employs the qualitative approach for collecting and analyzing the data of the study. Besides, it makes use of different exegeses of the Qur'ān to identify the differences in meaning between each pair of the Qur'ānic near-synonyms. The analysis of the data reveals that there exist some nuances between the pairs of Qur'ānic near-synonyms in terms of denotative and expressive meaning. The findings also show that the differences in meaning between the pairs of near-synonyms are not reflected in the English translations. Therefore, the study recommends that readers as well as translators should look for nuances between Qur'ānic near-synonyms whenever they find two words with similar meanings in order to perceive the Qur'ānic text appropriately and translatorsshould makeaneffort to reflect the nuances between the pairs of near-synonyms in their translation.